2014
DOI: 10.1074/jbc.m113.542340
|View full text |Cite
|
Sign up to set email alerts
|

Anti-amyloid Compounds Inhibit α-Synuclein Aggregation Induced by Protein Misfolding Cyclic Amplification (PMCA)

Abstract: Background: α-Synuclein filaments can be formed in vitro, but the process is slow and unreliable, unsuitable for high throughput screening.Results: Protein misfolding cyclic amplification (PMCA) rapidly assembles α-synuclein into filaments that form aggregates in cell culture and whose formation is inhibited by anti-amyloid compounds.Conclusion: Anti-amyloid compounds affect PMCA cell-transmissible α-synuclein fibril formation.Significance: α-Synuclein PMCA is useful for the screening of anti-aggregation compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 43 publications
6
70
0
Order By: Relevance
“…1B). The amyloid structure was furthermore supported by the circular dichroism (CD) spectra of the same fibrils, which showed a clear ␤-sheet signature (38) (Fig. 1C).…”
Section: Preparation and Immobilization Of Amyloid Fibers Onto Sprmentioning
confidence: 72%
“…1B). The amyloid structure was furthermore supported by the circular dichroism (CD) spectra of the same fibrils, which showed a clear ␤-sheet signature (38) (Fig. 1C).…”
Section: Preparation and Immobilization Of Amyloid Fibers Onto Sprmentioning
confidence: 72%
“…αSyn, like other amyloidogenic proteins assembles into fibrillar species in vitro under a range of solvent conditions and displays highly polymorphic mature fibrils [21,24,33,42,45]. Furthermore, aggregation kinetics of αSyn (wt and mutants) is known to be highly irreproducible and recently a number of studies have reported on new approaches to improve reproducibility of in vitro fibrillization assays [32,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…In each case, one single or very few specific host protein(s) or peptides like Tau, a-synuclein, superoxide dismutase 1 (SOD1), Tar DNA-binding protein 43 (TDP-43), prion protein (PrP) or b-amyloid peptide (Ab) misfolds from a soluble native conformation into a harmful aggregated state, rich in beta sheets [2][3][4][5][6][7][8][9][10][11][12]. Amplification of misfolding through seeded/nucleated polymerization leads to not fully defined toxic species and neuronal destruction.…”
Section: Introductionmentioning
confidence: 99%